Macroeconomic Effects of Raising Oil Prices: Insights from Morocco - Ritahi, Oussama; Echaoui, Abdellah (International Journal of Energy Economics and Policy, 2025)
This study examines the impact of Brent oil price shocks on key economic variables—namely inflation, GDP, exchange rate, trade openness, and unemployment rate using annual data from 1990 to 2022. The results of the study show that the variables considered under this study are cointegrated in the long-run which means that there is a relationship between these variables in the long-run. By employing a vector error correction model (VECM), we analyze the impulse response functions to understand the short- and long-term effects of oil price fluctuations on these economic indicators. Our findings reveal that Brent oil price increases lead to higher inflation and depreciation of the exchange rate, with both effects persisting in the short and long run. Conversely, GDP experiences a consistent negative impact from oil price hikes, suggesting a detrimental effect on economic growth over time. Trade openness shows a positive response, indicating increased trade activity due to rising oil prices. Additionally, the unemployment rate decreases in response to higher oil prices, reflecting a potential reduction in joblessness.